Variable Sequestration of Antifungals in an Extracorporeal Membrane Oxygenation Circuit. Issue 3 (8th September 2022) - Lyster, Haifa; Pitt, Timothy; Maunz, Olaf; Diamond, Suzanne; Roberts, Jason A.; Brown, David; Mills, Jeremy; Armstrong-James, Darius; Gerovasili, Vicky; Carby, Martin; Dunning, John; Simon, Andre; et al.
Abstract : Fungal infections are common and frequently associated with clinical failure in patients receiving extracorporeal membrane oxygenation (ECMO). Antifungal drugs have physicochemical characteristics associated with a higher likelihood of sequestration onto ECMO circuitry potentially leading to a subtherapeutic drug concentration. The percentage of sequestration of the antifungal drugs—caspofungin, posaconazole, and voriconazole—was determined using an ex vivo ECMO model. The circuits were primed with whole human blood, sodium chloride 0.9%, and human albumin solution. Serial 2 ml samples were taken at baseline, 0.5, 1, 2, 6, 12, and 24 hours after drug addition, paired with non-ECMO controls stored in a water bath at 37°C. Mean loss from the blood-primed ECMO circuits and controls at 24 hours relative to baseline were 80% and 61% for caspofungin ( p = ns), 64% and 11% for posaconazole ( p < 0.005), and 27% and 19% for voriconazole ( p < 0.05). Calculated AUC0–24 showed a 44% for caspofungin ( p = ns), 30.6% posaconazole ( p < 0.005), and 9% loss for voriconazole ( p = 0.003) compared with the controls, suggesting therapeutic concentrations of these antifungal agents cannot be guaranteed with standard dosing in patients on ECMO. Posaconazole exhibited the greatest loss to the ECMO circuit correlating with both high lipophilicity and protein binding of the drug.